2022
DOI: 10.1021/acs.macromol.2c01517
|View full text |Cite
|
Sign up to set email alerts
|

Suppressing the Hofmeister Anion Effect by Thermal Annealing of Thin-Film Multilayers Made of Weak Polyelectrolytes

Abstract: Thin films made of weak polyelectrolytes poly(allylamine hydrochloride) (PAH) and poly(acrylic acid) (PAA) have been fabricated on silicon wafers using the layer-by-layer (LbL) method. To study the influence of counteranion type on the growth and properties of PAH/PAA multilayers, the nature of the supporting sodium salt was varied from cosmotropic to chaotropic anions (F–, Cl–, and ClO4 –). Results of ellipsometry and AFM measurements indicate that the film thickness and surface roughness systematically incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…In an aqueous solution, the increased total area has few energetic consequences because the surface tension γ (or surface energy) is approximately zero. This was shown by surface force measurements with PE-covered surfaces. , However, in the air, the surface tension γ is between 15 and 25 mN/m, as adhesion and contact angle measurements show. ,, …”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…In an aqueous solution, the increased total area has few energetic consequences because the surface tension γ (or surface energy) is approximately zero. This was shown by surface force measurements with PE-covered surfaces. , However, in the air, the surface tension γ is between 15 and 25 mN/m, as adhesion and contact angle measurements show. ,, …”
Section: Resultsmentioning
confidence: 92%
“…34,51 However, in the air, the surface tension γ is between 15 and 25 mN/m, as adhesion and contact angle measurements show. 21,52,53 We suggested that pattern formation in PEMs is caused by minimizing mechanical stresses within the film. 18 Figure 6 demonstrates that the increased surface energy from exposure to air does not affect the surface pattern of PSS-terminated films.…”
Section: ■ Materials and Methodsmentioning
confidence: 99%
“…The water contact angle of F-532-10.4k also reached the contact angles of the atoms of O-532-11.6k and A-532-12.2k at 128 mJ/cm 2 , which is also unexpected. Unlike the solubility parameter, the wetting by water is a quite complex behavior that can be affected by many different parameters such as surface roughness and chain conformations. Especially during the PEB process, the surface concentrations of polar moieties, including carboxylic acid in the copolymer chains and generated acid molecules, can be varied, resulting in unexpected surface wetting properties with water molecules regardless of the variation in the comonomer structure. Therefore, these results suggest that the water contact angle is beneficial to catch if the deprotection reaction occurs by acid catalysis in the CAR mechanism, although the prediction of the patterning capability relying on it should be carefully considered.…”
Section: Resultsmentioning
confidence: 99%
“…The role of the ionic environment present in the reservoirs is of particular importance since ion-specific effects are responsible for the structural and physicochemical properties of polymer or polymer–surfactant solutions . The effect of the chemical composition of the electrolyte on the structure of polymers (or their charged version called polyelectrolytes) has already been reported in the past and was explained with the Hofmeister series of ions. Accordingly, the presence of kosmotropes (or water-structure-forming ions) stabilizes the conformation of well-hydrated polymeric chains, while chaotropes (or water-structure-breaking ions) disturb the hydrogen bonding pattern in polymer solutions and, hence, lead to the unfolding of the macromolecules . Despite its clear importance, such an ion-specific effect induced by dissolved salt constituents has rarely been studied and compared for EOR polymers.…”
Section: Introductionmentioning
confidence: 99%